Interaction mechanism of egg white- derived ACE inhibitory peptide TNGIIR with ACE and its effect on the expression of ACE and AT1 receptor - Zhipeng Yu; Hui Guo; David Shiuan; Chensi Xia; Wenzhu Zhao; Long Ding; Fuping Zheng; Jingbo Liu (Food Science and Human Wellness, 2020)
The egg white-derived hexapeptide TNGIIR inhibits angiotensin-converting enzyme (ACE) activity in vitro. In this work, molecular docking revealed that TNGIIR established hydrogen bonds with the S1 (Ala 354), S2 (Gln 281, His 513, Tyr 520 and Lys 511) and S1′ (Glu 162) pockets of ACE. In addition, the potential antihypertensive effect of the oral administration of TNGIIR in spontaneously hypertensive rats (SHR) was investigated, as was the effect of this peptide on the mRNA expression of ACE and angiotensin type 1 (AT1) and type 2 (AT2) receptors in renal tissue. The oral administration of TNGIIR (2, 10 and 50 mg/kg) for up to four weeks did not reduce the blood pressure of SHR, in contrast to captopril (10 mg/kg, orally), but attenuated the mRNA expression of ACE and AT1 receptor (as did captopril). In contrast, both TNGIIR and captopril enhanced the expression of AT2 receptor mRNA. There was no change in the circulating concentration of angiotensin I, but a slight decrease (about 10%) was seen in the concentration of circulating angiotensin II with TNGIIR and captopril. Keywords: Egg white proteins, ACE inhibitory peptide, Gene expression, Antihypertensive effect, Molecular docking